1998
DOI: 10.1002/(sici)1521-3773(19980817)37:15<2099::aid-anie2099>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedcis-Selective 1,4-Addition Reaction of Lower Order Cyanocuprates to Optically Active 5-(tert-Butyldimethylsiloxy)-2-cyclohexenone

Abstract: A remarkable cis selectivity has been observed in the 1,4-addition of lower order primary and secondary alkylcyanocuprates to 5-silyloxy- and 5-benzyloxy-substituted cyclohexenones. This enables the preparation of both enantiomers of the corresponding 5-alkyl-substituted cyclohexenones (S)- and (R)-3 by the reaction of the readily available 5-(tert-butyldimethylsiloxy)-2-cyclohexenone (1) with either the lower or higher order cyanocuprate. DBU=1,8-diazabicyclo[5.4.0]undec-7-ene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…24 (R = OSiBu t Me 2 ). 27 Theoretical studies have not yet been applied to this latter system but the observed stereochemical outcome can be rationalised by the intramolecular co-ordination in transition state C.…”
Section: Copper(iii) Vs Carbocuprationmentioning
confidence: 99%
“…24 (R = OSiBu t Me 2 ). 27 Theoretical studies have not yet been applied to this latter system but the observed stereochemical outcome can be rationalised by the intramolecular co-ordination in transition state C.…”
Section: Copper(iii) Vs Carbocuprationmentioning
confidence: 99%
“…The diastereoselectivity of the chelation-controlled conjugate additions to 10 complements most organocopper-based additions to C-5 substituted enones . Stereoselective additions to C-5 oxygenated enones have most often employed cyclic acetals ( 26 ) in which the nucleophilic attack is sterically biased to one face of the enone, although highly selective conjugate additions of organocopper reagents were recently achieved with the C-5 TBDMSO-substituted enone 27 . We reasoned that organocopper additions to silylated oxo−nitriles ( 28 ) would provide conjugate adducts diastereomeric to those obtained by chelation control, since the silyl group would effectively bias the nucleophilic addition through the combined influence of steric and stereoelectronic constraints.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the sparse use of C-5 ether-substituted enones, , alkyl substituents are routinely employed in stereoelectronically controlled conjugate additions . We demonstrated the use of aldols in sequential conjugate additions by eliminating 34a with n -Bu 4 NF, to provide the C-5-substituted enone 36 (eq 4).…”
Section: Resultsmentioning
confidence: 99%
“…Enantiomerically enriched cyclohex-2-enone derivatives are extremely useful building blocks for the preparation of biologically active compounds, including natural products. Among the various types of cyclohex-2-enone derivatives, 5-hydroxy- and 5-alkoxycyclohex-2-enones represent the most attractive and versatile chiral building blocks, and several approaches for their synthesis have been proposed. , The two 5-siloxycyclohex-2-enones 1 and 2 and bicyclic compounds 3 and 4 are the only enantiomerically enriched 6-alkyl-substituted 5-hydroxycyclohex-2-enone derivatives reported thus far. …”
mentioning
confidence: 99%